Rural Tourism Products and Environmental Management - Lisbet Eunice Pérez Anzardo; Migdely Barbarita Ochoa Avila; Irina Reyes Martínez; Rodolfo González Ortega; Eduardo Estrabao Morales (BIRCU, 2021)
Rural tourism generates a set of human relationships resulting from the visit of tourists to peasant communities that take advantage of and enjoy the environment, natural, cultural, patrimonial and socio-productive values. The negative impacts that conventional tourism generates on the ecosystem has motivated the management of tourist destinations in such a way that responsibility and sustainability prevail, so that tourists can accumulate experiences in open air and in direct contact with the environment without damaging it encouraging localities to achieve prospective development. The commitment of the country and tourism has been to preserve the environment, but their management has not been enough to guarantee sustainability and comprehensiveness from a local perspective. The general objective of this research is to expose the theoretical foundation of environmental management in Cuba, and propose good practices in the implementation of rural tourism products; that guarantee sustainable natural and cultural heritage. Various theoretical methods were used such as analysis and synthesis, historical-logical, systemic structural; and some empirical ones such as scientific observation, interview, and study of the normative documents of the tourist process, among others. Statistical methods were also used for information processing, as well as the triangulation of sources and methods. As a result, the bases were laid for the theoretical-practical deepening of the research and actions are proposed to contribute to the conservation of the environment through the promotion of rural tourism products.but their management has not been enough to guarantee sustainability and comprehensiveness from a local perspective.